2009
DOI: 10.1160/th08-06-0396
|View full text |Cite
|
Sign up to set email alerts
|

Vascular events in Korean patients with myeloproliferative neoplasms and their relationship to JAK2 mutation

Abstract: SummaryEvaluation of the Janus kinase 2 (JAK2) V617F mutation has been widely used for the diagnosis of myeloproliferative neoplasms (MPN). However, its prognostic relevance to clinical outcome is not completely understood. We investigated the association of JAK2 V617F with vascular events in Korean patients with myeloproliferative neoplasms (MPN). We studied 283 patients from 15 centers, who were diagnosed with MPN. The JAK2 V617F status was evaluated by allele-specific polymerase chain reaction (PCR) and seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
2
21
0
1
Order By: Relevance
“…The patient with ET with homozygous JAK2 V617F had, indeed, a long history of ET. A recent study in Korea also found that the JAK2 V617F homozygous mutation was more significantly related to an increased risk of thrombosis in MPN (Bang et al. , 2009).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The patient with ET with homozygous JAK2 V617F had, indeed, a long history of ET. A recent study in Korea also found that the JAK2 V617F homozygous mutation was more significantly related to an increased risk of thrombosis in MPN (Bang et al. , 2009).…”
Section: Discussionmentioning
confidence: 88%
“…The lower frequency of JAK2 V617F mutation in our data as compared with previous studies (Table 2) is hard to explain. Korean patients with MPN had similar frequencies of JAK2 mutation and occurrence of vascular events as compared to Western patients (Bang et al. , 2009; Cho et al.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our study, ROC analysis of thrombotic events revealed that the age at which thrombosis would occur was 60.5, supporting the practice to use 60 as the common cutoff of age. More recently, JAK2V617F mutation and allele burden are becoming better recognized as risk factors in both Asian and Caucasian subjects with nearly doubling of odds ratio for thrombosis in mutated individuals (22)(23)(24)(25)(26)(27)(28)(29)(30). In a cohort of 224 patients with ET, JAK2V617F mutation increased the relative risk of overall thrombosis by 45% (26).…”
Section: Discussionmentioning
confidence: 99%